Минималь зүүн-баруун тэгш хэмт загварт мюон аномаль соронзон моментын тооцоо: Calculation of the muon anomalous magnetic moment in the minimal left-right symmetric model - Tumurjav, lkhagvajav; Tsedenbaljir, Enkhbat (Scientific transaction of the National University of Mongolia. Physics, 2024)
Бид энэ ажилд мюоны аномаль соронзон моментыг стандарт моделийн нэгэн өргөтгөл болох минималь зүүн-баруун тэгш хэмт загварт судлав. Ингэхдээ хүнд гейж бозон мюон аномаль соронзон моментод хэрхэн нөлөөлж буйг тооцсон. Тооцооны үр дүнгээр стандарт онолын таамаглал ба Мюон g-2 коллаборацын туршилтын утга хоорондын 4.2σ зөрүүд тайлбар өгөв. [English] In this work, we study the anomalous magnetic moment of the muon within the minimal left-right symmetric model, an extension of the Standard Model. In doing so, we calculate how the heavy gauge bosons affect the muon anomalous magnetic moment. The calculation results explains the difference between the Standard model theoretical prediction and the experimental value from Muon g-2 collaboration at 4.2σ standard deviations.